THE STUDENTS’ PERSONALITY BASED ON THEIR READING ATTITUDE - Mona Kaforina; Mulyadi Mulyadi; Aswadi Jaya (Universitas PGRI Palembang, 2024)
This research aimed to know and analyze students’ personalities based on their reading attitudes and identify the reading strategies frequently used by students. The research was conducted at SMP PGRI 1 Palembang using a qualitative method. The data were collected through observation, surveying using two questionnaires (a personality questionnaire and a reading strategy questionnaire), interviews, and documentation. The research sample consisted of 30 students from class VIII.1 at SMP PGRI 1 Palembang in the academic year 2022–2023, even semester. Based on this research, it was found that 24% of students in class VIII.1 have a conscientiousness personality characterized by being organized, responsible, and disciplined. Furthermore, 43% of students use a global reading strategy that focuses on overall text comprehension. These findings indicate a relationship between reading attitude and students’ personalities, with conscientiousness and global reading strategy dominating. The implication is that this research provides important insights for the development of effective learning strategies to enhance students’ reading skills at SMP PGRI 1 Palembang.